1998
DOI: 10.1007/bf02737811
|View full text |Cite
|
Sign up to set email alerts
|

Purification and physical characterization of cloned human cAMP phosphodiesterases PDE-4D and-4C

Abstract: Individual isozymes of family four cyclic-nucleotide phosphodiesterases (PDE-4s) were characterized and compared in order to advance our understanding of how PDE-4s regulate cAMP levels in cells. Full-length and shorter clones containing various functional domains were constructed and overexpressed using a recombinant baculovirus-infected Sf9 insect cell system. One form each of PDE-4C and 4D was purified 125- and 534-fold, respectively, using anion-exchange and affi-gel blue chromatography. The purified mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
1
1
Order By: Relevance
“…Previous studies, including our own, showed by gel filtration and density gradient centrifugation that the catalytic domains of PDE4A and PDE4B behave as oligomers (40,(42)(43)(44). As the catalytic domains of the PDE4 subtypes are highly conserved, it is unlikely that this discrepancy is due to sequence differences between PDE4A/B and the PDE4D used in our present study.…”
Section: Table I Physicochemical Properties Of the Pde4d Constructscontrasting
confidence: 39%
“…Previous studies, including our own, showed by gel filtration and density gradient centrifugation that the catalytic domains of PDE4A and PDE4B behave as oligomers (40,(42)(43)(44). As the catalytic domains of the PDE4 subtypes are highly conserved, it is unlikely that this discrepancy is due to sequence differences between PDE4A/B and the PDE4D used in our present study.…”
Section: Table I Physicochemical Properties Of the Pde4d Constructscontrasting
confidence: 39%
“…advantage of speed, economy, and efficacy compared to alternative expression systems such as the baculovirus system (17,18,23). All PDE4A constructs were found to be expressed as inclusion bodies and no free enzymatic activity could be detected.…”
Section: Figmentioning
confidence: 96%